Integration of didactical knowledge and mathematical content knowledge in pre-service teacher training (2004)
We suggest some ideas about how content knowledge and didactical knowledge could be integrated in pre-service secondary mathematics teachers' training. We identify the activities we expect a teacher to perform when planning a lesson and determine the didactical knowledge that she has to put into play in order to do so. We then show the relationship between that didactical knowledge and the corresponding content knowledge.